Exercise in the heat: strategies to minimize the adverse effects on performance - Terrados, N.; Maughan, R. J. (Journal of Sports Sciences, 1995)
Exercise in the heat is usually associated with reduced performance; both dehydration and hyperthermia adversely affect mental and physical performance. For athletes from temperate climates, the negative effects of heat had humidity can be attenuated by a period of acclimatization. This requires up to 10-14 days. Endurance-trained individuals already show some of the adaptations that accompany acclimatization, but further adaptation occurs with training in the heat. Prior dehydration has a negative effect even on exercise of short duration where sweat losses are small. The athlete must begin exercise fully hydrated and regular ingestion of fluids is beneficial where the exercise duration exceeds 40 min. Dilute carbohydrate-electrolyte (sodium) drinks are best for fluid replacement and also supply some substrate for the exercising muscles. Post-exercise rehydration requires electrolyte as well as volume replacement. In extreme conditions, neither acclimatization nor fluid replacement will allow hard exercise to be performed without some risk of heat illness.